Integração energética da etapa de extração de óleo de soja, utilizando a análise Pinch - Fernandes Junior, Carlos Coutinho (2009)
In the process of soy oil the consumption of energy is extremely high, which is always important to create new alternatives to energetic consumption reduction. This paper is carried on a case study of energetic integration in a soy oil factory operating with an average production of 15.000 tons/month. At first, the rate of flow, the input and output temperatures and the calorific capacity of all currents in the extraction phase were evaluated. After this assessment, based on the thermal potential change, four currents were selected, two denominated hot currents and two denominated cold currents. The first hot current (Q1) consists of a crude oil current from the post-separation phase of the solvent hexane with the input temperature of 110 ºC and output temperature of 80ºC. The second hot current (Q2) consists of a water current coming out of a boiler with an input temperature of 90 ºC and goes to the effluent treatment station having to be cooled to 55 ºC. These two currents have a thermal potential change of 262,8 kW/h. The third current denominated cold current F1, consists of a water current that comes from the decanter with a input temperature of 40 ºC and enters in the heater to reach an output temperature of 90 ºC, where the residual hexane is evaporated. The fourth current, denominated cold current F2, is a mixture of 70% of oil and 30% of hexane with an input temperature of 60 ºC and output temperature of 90 ºC. These two currents have a thermal necessity of 330 kW, for their heating. The synthesis methodology adopted for the heat exchangers network synthesis, due to the easiness in application and interaction with the user, was the Pinch Analysis. In the synthesis procedure, the Problem Table was developed and the Pinch Point was identified and the goals for the consumption of utilities were obtained for the maximum energy recovery. The problem was divided into two regions, below and above the Pinch Point. After the synthesis and optimization, the total cost for the network was calculated and all thermal exchange occurs above the Pinch Point . The proposed network consists of two heat exchangers and two boilers, so that a exchanger performs the thermal change between the Q1 (crude oil) and Q2 (miscela) currents. The second exchanger performs the change between Q2 (the water in the boiler exit) and F1 (water in the decanter exit) currents. The additional heating for the cold currents to reach final temperatures is provided by the boilers that are already being used in the factory. The economy generated by the reduction in the consumption of utilities was of R$ 91,000.00/year, meaning a reduction of steam consumption of 79,6% and a reduction of 5,3% in the global consumption of the plant steam. The investment needed for the two proposed heat exchangers in the network, is R$ 16.540,00. Evaluating the year total cost, that includes the annual capital cost of the exchangers, an annual reduction of R$ 114.445,00 for R$ 25.800,00 is verified corresponding to 77.5% reduction in the annual total cost after the network synthesis. The return rate for the investment proposed is only 3 months. Therefore, Pinch Analysis is confirmed to be efficient in the energetic integration of processes reaching meaningful economy results in thermal energy, contributing for the industrial processes that are more and more competitive.